2020
DOI: 10.3390/ijerph17061969
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Sensorineural Hearing Loss as a Result of Exposure to Air Pollution

Abstract: Whether exposure to air pollution is associated with developing sensorineural hearing loss (SHL) remains controversial. Using data from the National Health Insurance Research Database, we recruited a total of 75,767 subjects aged older than 20 years with no history of SHL from 1998 to 2010, and they were followed up until SHL was observed, they withdrew from the National Health Insurance program, or the study ended. The subjects were evenly exposed to low-level, mid-level, and high-level carbon monoxide (CO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Several studies indicated that exposure to NO 2 could be related to hearing problems. Chang et al (2020) found that people exposed to moderate (hazard ratio, HR = 1.40, 95% CI 1.27–1.54) and high levels of NO 2 (HR = 1.63, 95% CI 1.48–1.81) were at higher risk of developing sensorineural hearing loss than those exposed to the low level. The results of Tsai et al (2020) were similar, finding a significantly increased risk of SSNHL in those exposed to high concentrations of NO 2 (adjusted HR = 1.02, 95% CI 1.01–1.04).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies indicated that exposure to NO 2 could be related to hearing problems. Chang et al (2020) found that people exposed to moderate (hazard ratio, HR = 1.40, 95% CI 1.27–1.54) and high levels of NO 2 (HR = 1.63, 95% CI 1.48–1.81) were at higher risk of developing sensorineural hearing loss than those exposed to the low level. The results of Tsai et al (2020) were similar, finding a significantly increased risk of SSNHL in those exposed to high concentrations of NO 2 (adjusted HR = 1.02, 95% CI 1.01–1.04).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study ( Tsai et al, 2020 ) found that participants exposed to fine particulate matter (PM 2.5 : particulate matter ≤ 2.5 μm in diameter) and nitrogen dioxide (NO 2 ) had a substantially increased risk of sudden sensorineural hearing loss (SSNHL). Another study ( Chang et al, 2020 ) showed that increased concentrations of NO 2 were linked to a higher risk of sensorineural hearing loss, while in a nested case-control study ( Choi et al, 2019 ), SSNHL was associated with NO 2 exposure, but particulate matter with a diameter of 10 μm or less (PM 10 ) was not associated with SSNHL. Similarly, another study ( Lee et al, 2019 ) also found no association between PM 10 and number of SSNHL patient.…”
Section: Introductionmentioning
confidence: 99%
“…The air quality data are managed by Taiwan Environmental Protection Administration. The annual concentrations of PM 2.5 , SO 2 , CO, NO, and NO 2 from 1998 to 2010 were classi ed into the three levels according to tertiles: the PM 2.5 concentrationsof the low-, mid-, and high-level groups were<30.29 (μg/m 3 ), 30.29-37.61 (μg/m 3 ) and >37.61 (μg/m 3 ), respectively.the SO 2 concentrationsof the low-, mid-, and high-level groups were<3.57 (ppb), 3.57-5.51 (ppb) and >5.51 (ppb), respectively.the CO concentrationsof the low-, mid-, and high-level groups were<0.61 (ppm), 0.61-0.76 (ppm) and >0.76 (ppm)respectively.the NO concentrationsof the low-, mid-, and high-level groups were<5.04 (ppb), 5.04-8.90 (ppb) and >8.90 (ppb), respectively.the NO 2 concentrationsof the low-, mid-, and high-level groups were<19.48 (ppb), 19.48- 25.55 (ppb) and >25.55 (ppb), respectively.…”
Section: Exposure Measurementmentioning
confidence: 98%
“…(24)A previous studyreports air pollution as a risk factor ofdeveloping sensorineural hearing loss. (25)However, the association between exposure to air pollution and SSNHL has not been extensively discussed in the literature. Therefore, we conducted this nationwide study to evaluate the risk of SSNHL in Taiwanese residents with exposure to air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to air pollution increases oxidative stress, which can play an important role in endothelial dysfunction [24]. A previous study reports air pollution as a risk factor of developing sensorineural hearing loss [25]. However, the association between exposure to air pollution and SSNHL has not been extensively discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%